Terrorism in time of the pandemic: exploiting mayhem - Arie W. Kruglanski; Rohan Gunaratna; Molly Ellenberg; Anne Speckhard (Taylor & Francis Group, 2020)
Despite the world's overwhelming preoccupation with the COVID-19 pandemic, the threat of international and domestic terrorism is not in decline according to available indicators. The angst that the pandemic induced in millions of people, and the incapacitation of major functions and institutions of world's societies are exploited by both jihadist and far-right terror organisations for the spread of conspiracy theories aimed to fuel hate against their alleged nemeses, the encouragement of easy attacks against vulnerable targets, and the spread of bedlam and confusion intended to bring down governments and promote the terrorists' agenda. In this paper, we illustrate and discuss terrorism trends manifest during the COVID-19 pandemic and consider the threat these trends pose to the world's security.